Dust-storm induced cross-polarization at MMW dands in Northern Nigeria - Musa, A.A; Bashir, Saad Osman; Islam, Md. Rafiqul; Khalifa, Othman Omran (2012)
Sand and Dust storms have the potentiality of causing microwave degradation for substantial percentage of time which can lead to drop in the availability and quality of services rendered by communication systems. This paper investigates induced cross-polarization by dust storms at MMW bands. It introduces a model factor to calculate phase shift and attenuation which are to be used as inputs to cross-polarization discrimination (XPD) computation. A parametric analysis of sand and dust storm in northern Nigeria was carried out and its effect on MMW band propagation.